Freedom of Speech Without a Direction: Criticism of the Promotion of Freedom of Speech in Indonesia - Sayuti, Sayuti; Effendi, Ghina Nabilah; Yanti, Illy (Al-Risalah, 2023)
The attempt to equate freedom of speech with other rights, such as freedom of expression or opinion, is misguided because these rights have distinct realms concerning their promotion and resolution of legal violations. In practice, this misconception persists in Indonesia, where there is no specific law dedicated to regulating freedom of speech. Therefore, this study explored the factors that lead to legal vacuum for freedom of speech and provided solutions to overcome this vacuum. This study also assessed the various legal frameworks and practices concerning the promotion of freedom of speech in Indonesia after the 1998 Reform Era using a normative juridical approach. The result showed that legal vacuum in promoting the right to freedom of speech attributed to the conflicting priorities of human rights and the ambiguity surrounding the understanding of freedom of expression. It is important to synchronize laws and regulations regarding the rights belonging to freedom of expression and strengthen the associated regulation that specifically contain definitions, limitations, and ways of resolving violations of the law. This process provided a detailed legal direction or umbrella for efforts to promote freedom of speech.